2013
DOI: 10.1186/1556-276x-8-516
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature synthesis of zinc oxide nanoparticles in different media and their application in cyanide photodegradation

Abstract: Cyanide is an extreme hazard and extensively found in the wastes of refinery, coke plant, and metal plating industries. A simple, fast, cost-effective, room-temperature wet chemical route, based on cyclohexylamine, for synthesizing zinc oxide nanoparticles in aqueous and enthanolic media was established and tested for the photodegradation of cyanide ions. Particles of polyhedra morphology were obtained for zinc oxide, prepared in ethanol (ZnOE), while spherical and some chunky particles were observed for zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 40 publications
1
58
1
1
Order By: Relevance
“…4 shows TEM (transmission electron microscopy) images and SAED (selected area electron diffraction) patterns of ZnO nanocrystals. Bagabas et al [19] reported that clear morphology was observed for the calcined samples and not in the case of uncalcined samples. But, it is clearly observed from the images that the particles have hexagonal (wurtzite) structure and average particle size of the nanocrystals synthesized by method I was smaller than the nanocrystals by method II.…”
Section: Resultsmentioning
confidence: 95%
“…4 shows TEM (transmission electron microscopy) images and SAED (selected area electron diffraction) patterns of ZnO nanocrystals. Bagabas et al [19] reported that clear morphology was observed for the calcined samples and not in the case of uncalcined samples. But, it is clearly observed from the images that the particles have hexagonal (wurtzite) structure and average particle size of the nanocrystals synthesized by method I was smaller than the nanocrystals by method II.…”
Section: Resultsmentioning
confidence: 95%
“…Intensive studies have been done on various factors, such as precursor concentrations [8,9], temperature [10,11], duration [12], surfactant concentration [7], dopant concentration [6], solvent medium [13], pH of reaction mixture [14] and source of light during synthesis [15], which individually and collectively affect the shape, size and optical properties of ZnO. Various researchers [16][17][18] suggested that NaOH concentration plays a vital role in determining the morphology, size and optical bandgap of obtained nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…It is quite obvious that the extent of porosity (V p: Z 2 > Z 4 > Z 1 > Z 8) and not the pore size (D p: Z 2 > Z 4 > Z 1 ≈ Z 8) is the determining factor for the S BET (NPs with needle-like shape have the highest V p). It is also noticeable that the ZnO synthesized in microemulsion possess V p much higher than those prepared in other polar solvents such as water or ethanol [19]. The doublet Zn 2p spectrum in Figure 5 shows binding energies of 1,021.1 and 1,044.2 eV, which referred to Zn-2p3/2…”
Section: Samples Bet(m2 G−1)d P(nm)v P(cm3 G−1)l (Nm)ad (Nm)mentioning
confidence: 95%